Surface modified cross-linked poly(vinyl alcohol)/poly(vinyl pivalate) suspension particles - D Aguiar, Donna-Leigh (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2010.